Rootstock Sub-Optimal Temperature Tolerance Determines Transcriptomic Responses after Long-Term Root Cooling in Rootstocks and Scions of Grafted Tomato Plants - Ntatsi, Georgia; Savvas, Dimitrios; Papasotiropoulos, Vassilis; Katsileros, Anastasios; Zrenner, Rita M.; Hincha, Dirk K.; Zuther, Ellen; Schwarz, Dietmar (Frontiers in Plant Science, 2017)
Grafting of elite cultivars onto tolerant rootstocks is an advanced strategy to increase tomato tolerance to sub-optimal temperature. However, a detailed understanding of adaptive mechanisms to sub-optimal temperature in rootstocks and scions of grafting combinations on a physiological and molecular level is lacking. Here, the commercial cultivar Kommeet was grafted either onto ‘Moneymaker’ (sensitive) or onto the line accession LA 1777 of Solanum habrochaites (tolerant). Grafted plants were grown in NFT-system at either optimal (25°C) or sub-optimal (15°C) temperatures in the root environment with optimal air temperature (25°C) for 22 days. Grafting onto the differently tolerant rootstocks caused differences in shoot fresh and dry weight, total leaf area and dry matter content of roots, in stomatal conductance and intercellular CO2 and guaiacol peroxidase activity but not in net photosynthesis, sugar, starch and amino acid content, lipid peroxidation and antioxidant enzyme activity. In leaves, comparative transcriptome analysis only identified differentially expressed genes responding to sub-optimal root temperature when ‘Kommeet’ was grafted onto the sensitive but not onto the tolerant rootstock. 1509 and 2046 differentially expressed genes responding to sub-optimal temperature were identified in LA 1777 and ‘Moneymaker’ rootstocks, respectively. In tolerant rootstocks down-regulated genes were enriched in main stress-responsive functional categories and up-regulated genes in cellulose synthesis suggesting that cellulose synthesis may be one of the main adaptation mechanisms to long-term sub-optimal temperature. Down-regulated genes of the sensitive rootstock showed a similar response, but functional categories of up-regulated genes pointed to induced stress responses. Down-regulated genes of the sensitive rootstock showed a similar response, but functional categories of up-regulated genes pointed to induced stress responses. Rootstocks of the sensitive cultivar Moneymaker showed in addition an enrichment of up-regulated genes in the functional categories fatty acid desaturation, phenylpropanoids, biotic stress, cytochrome P450 and protein degradation, indicating that the sensitive cultivar showed more transcriptional adaption to low temperature than the tolerant cultivar that did not show these changes. Mainly defense-related genes were highly differentially expressed between the tolerant and sensitive rootstock genotypes under sub-optimal temperature. These results provide new insights into the molecular mechanisms of long-term sub-optimal temperature tolerance of tomato.